Mentimeter for Arabic Writing: Analysis of Morphological and Syntactic Errors of Islamic University Students - Ritonga, Apri Wardana; Hasibuan, Renni; Desrani, Ayu; Ayad, Nahid (Journal Of Foreign Language Learning and Teaching, 2024)
The advent of modern technology has facilitated Arabic language learning but also poses challenges in mastering morphology and syntax. This study aims to analyze morphological and syntactic errors in Arabic writing among university students using the Mentimeter application. Employing a qualitative error analysis method, data were collected through interviews and written responses on Mentimeter. The findings reveal several dominant grammatical errors, including issues with hamzah qata' and hamzah wasl, idhafah, and gender agreement in numbers (adad and ma'dud). The most frequent error involved the writing of hamzah, highlighting the need for focused instruction. Additional errors in na‘at-man‘ut structures, possessive pronouns, and prepositions reflect the syntactic challenges students face. This study recommends structured grammatical exercises, explicit teaching of qawa